2015
DOI: 10.2196/resprot.4037
|View full text |Cite
|
Sign up to set email alerts
|

An Integrated Web-Based Mental Health Intervention of Assessment-Referral-Care to Reduce Stress, Anxiety, and Depression in Hospitalized Pregnant Women With Medically High-Risk Pregnancies: A Feasibility Study Protocol of Hospital-Based Implementation

Abstract: BackgroundAt prevalence rates of up to 40%, rates of depression and anxiety among women with medically complex pregnancies are 3 times greater than those in community-based samples of pregnant women. However, mental health care is not a component of routine hospital-based antenatal care for medically high-risk pregnant women.ObjectiveThe purpose of this study is to evaluate the effectiveness and feasibility of the hospital-based implementation of a Web-based integrated mental health intervention comprising psy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 91 publications
0
17
0
3
Order By: Relevance
“…Thus an intervention administered during pregnancy may also prevent the development and/or progression of antenatal depression to postpartum depression following childbirth. Whilst there is preliminary evidence that CCBT interventions are acceptable during pregnancy [ 51 ], further studies are needed to investigate the impact of such an intervention during pregnancy [ 33 , 52 , 53 ]. Our review would also suggest there is a need for more rigor in this field, particularly harmonisation of symptom scores used to allow future meta-analyses of outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus an intervention administered during pregnancy may also prevent the development and/or progression of antenatal depression to postpartum depression following childbirth. Whilst there is preliminary evidence that CCBT interventions are acceptable during pregnancy [ 51 ], further studies are needed to investigate the impact of such an intervention during pregnancy [ 33 , 52 , 53 ]. Our review would also suggest there is a need for more rigor in this field, particularly harmonisation of symptom scores used to allow future meta-analyses of outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…A CCBT resource for the self-management of perinatal depression could therefore represent an efficacious, accessible and economically sound resource [ 32 ]. CCBT also provides a level of anonymity not possible in clinical care, can be accessed at a time and place suitable for the participant and can be adapted to different cultures, languages and literacy levels to ensure the inclusion of vulnerable groups [ 33 ]. However, before CCBT is embedded in clinical practice for treatment of perinatal depression, there is a need for a systematic review of the existing evidence to determine whether web-interventions for pregnant and post-partum women are efficacious for prevention and treatment of perinatal mood disorders and potentially to inform the design of future studies if gaps in the current evidence base are identified.…”
Section: Introductionmentioning
confidence: 99%
“…An intervention of home-based personalized reminiscence, supported by a program of training and a novel iPad app, was examined for preliminary efficacy using 3 outcome measures pertaining to mutuality, emotional well-being, and quality of carer-patient relationships. The quasi-experimental design is appropriate and a common design for assessing the feasibility of novel technological interventions [ 37 - 39 ]. In line with quality standards, repeated measures testing was employed.…”
Section: Methodsmentioning
confidence: 99%
“…Depression, anxiety, and stress affect 15%–25% of women during pregnancy [1] and disproportionately affect minority and immigrant populations [2]. Chronic stress because of poverty, low socioeconomic position, or racism poses further challenges to women during the puerperium [3], and although considered a natural event in a woman’s lifespan, pregnancy can be fraught with adversity and risk.…”
Section: Introductionmentioning
confidence: 99%